PATTERN OF BREAST CANCER: EXPERIENCE AT LADY READING HOSPITAL, PESHAWAR - Naeem, Muhammad; Khan, Nadim; Aman, Zahid; Nasir, Amir; Samad, Ambreen; Khattak, Abbas (Journal of Ayub Medical College Abbottabad, 2008)
Background: Breast Cancer is the commonest malignancy of females all over the world and second leading cause of death due to cancer among females. The aim of this Descriptive study was to see the various features of breast cancer in order to know the pattern of disease in the recent time. The study was conducted from Jan. 2007 to Dec. 2007 in Surgical C Unit, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar, Pakistan. Methods: Study included all patients presenting to and admitted in Surgical C Unit LRH, with carcinoma of breast during the above mentioned period. Name, age, sex, other relevant data, history and examination findings and results of histopathology and other investigations were recorded. Results: Total of 46 patients was included in the study, out of which there were 46 female and 1 male patients. Most common age group was 40-49 years with 14 patients, followed by 50-59 years with 12 patients. Most common type of carcinoma was infiltrating ductal carcinoma with no specific features with 38 patients. Other types included 2 infiltrating ductal carcinomas of papillary type, 1 mucinous type and 1 medullary type; 3 invasive lobular carcinomas, and 1 mixed lobular and ductal carcinoma. The disease was left sided in 24 cases, right sided in 20 cases while it was bilateral in 2 cases. Upper outer quadrant of the breast was most commonly involved (n=26). There were 2 cases of stage I, 16 stage II, 20 stage III and 08 cases of stage IV disease. There were 2 cases of grade I, 16 grade II, and 28 cases of grade III. Conclusion: Carcinoma breast is still a common problem presenting at a young to middle age group with invasive ductal carcinoma being the commonest variant with a high grade and a late stage of presentation due to lack of screening and awareness programs. Keywords: Breast carcinoma